Інформаційна держава як концепція новітньої доби - Жуков, Є.В. (Альманах права, 2012)
Стаття присвячена дослідженню перетворень у розумінні ідеальної держави з огляду на сучасні процеси енергетично-технічної комунікації. Центральна увага в публікації приділяється визначенню основних чинників, що актуалізують потребу нової моделі ідеальної держави в умовах поточної «кременевої» доби та формулювання концепції новітньої інформаційної держави. Статья посвящена исследованию преобразований в понимании идеального государства с учетом современных процессов энерготехнологической коммуникации. Основное внимание в публикации уделяется определению основных факторов, актуализирующих необходимость новой модели идеального государства в условиях современной «кремниевой» эпохи и формулированию концепции новейшего информационного государства. This article is dedicated to research of transformations in understanding of an ideal state model in modern processes context of energy and technology communication. The main attention in this publication is given to definition of basic factors, which actualizing necessity of a new ideal state model in conditions of modern “silicon”
age and to formulating concept of the newest information state. Both new possibilities and new threats for public life are created by the present stage of civilization development. In the information sphere, which is getting the status of the public communication dominant sphere as the thoughts of professionals are generalized there, the following aspects may be referred to the threats: organizational
(inability to quickly process the information field, make the timely required decisions and implement them), institutional (unavailability of the governmental bodies efficient system, which could provide for an effective level of information security), ideological (correspondingly internal and external vectors in the efficient work of the state
authorities with public conscience), educational (lack of education for production of quality information product on the side of the state, both on the level of “intercourse” with the public and on the level of the universal social values promotion) and cybernetic (dissemination of information by means of the modern facilities of information
and technical communication, in particular by means of the worldwide Internet, and increasing share of electronic commerce and denationalization of the electronic sector of the national economy for the purpose of bringing incomes from under the taxation helmet, which causes considerable expansion of the limits of each person real
freedom that becomes less dependable on the state complicating the country administrative process and promoting political inactivity, anarchism, etc.).
As for the new possibilities and their potential, they become apparent, first of all, on the following levels: political (optimization of the state functioning form towards electronic one, which substantially decreases the weight of bureaucracy and complement of the state workers); economic (new markets penetration, creation of electronic
product with low cost as regards the results of in tellectual and creative work; increased possibilities for self-sufficient participation in the market of small and medium business representatives); social (formation of strong middle class as the level of knowledge and professional competence of an individual come to the front, not the capital); ideological
(formation of actually pluralistic information field that will be eliminating the possibility for the state to manipulate the public conscience; formation of a politically autonomous personality capable of deliberate political choice); and epistemological (increase of the population education common level through the widened accessibility to education
and cognitive process in general including the disabled people). On the basis of the analysis of the existing semantic field that has formed under the influence of the modern
information and technical communication processes it may be concluded that the latter do not answer the requirements of today to the full extent, especially as regards the institutional and corresponding legal transformations conditioned by the above mentioned processes. It is such underworked moments, as well as the inheritance and continuation of ontology of the social lawful state, that have become the basis of possibility to formulate a new modern doctrine of the state, the information state.
The information state continues the ideological principles of the democratic social and political order whose sense has already been laid down by Hegel with determination of a state as rational reality, which should not be identified with ideal. Reality of freedom accessible to man of present development whose limits progress together
with man itself. The information state concentrates on providing the man of present development with its freedom of modern level that will satisfy the requirements of its present level of civilization development both technologically (being relative to the notion of electronic state) and institutionally (formation of the fourth information and supervising
power, which will efficiently form and realize the latest scientific and technical achievements in order to facilitate the interaction between the state and civil society, increase the level of legality and law and order, make the power more transparent and understandable in the course of its activity, etc.). Thus, contemporaneity has reached a state when the need in transformation, revision and amendment of the existing ideal structures of the lawful electronic state has objectively become burning, and demands finding absolute doctrinal expression in a new concept of the information state.